A new autoinhibited kinase conformation reveals a salt-bridge switch in kinase activation - Wei, Qiang (Sci Rep, 2016)
In the structure of autoinhibited EphA2 tyrosine kinase reported herein, we have captured the entire activation segment, revealing a previously unknown role of the conserved Arg762 in kinase autoinhibition by interacting with the essential Mg(2+)-chelating Asp757. While it is well known that this Arg residue is involved in an electrostatic interaction with the phospho-residue of the activation loop to stabilize the active conformation, our structure determination revealed a new role for the Arg, acting as a switch between the autoinhibited and activated conformations. Mutation of Arg762 to Ala in EphA2 sensitized Mg(2+) response, resulting in enhanced kinase catalytic activity and Mg(2+) cooperativity. Furthermore, mutation of the corresponding Arg/Lys to Ala in PKA and p38MAPK also exhibited similar behavior. This new salt bridge-mediated switch may thus be an important mechanism of activation on a broader scope for kinases which utilize autophosphorylation.